Building noble morals through worship: a study from Buya Yahya and Ustadz Adi Hidayat - Satra, Alihan; Ramadhan, Rahmad; Nazhifah, Nazhifah; Rahmadani, Novi (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
The paper